2020
DOI: 10.1590/1413-7054202044004920
|View full text |Cite
|
Sign up to set email alerts
|

Multispectral aerial images for the evaluation of maize crops

Abstract: ABSTRACT The combination of multispectral aerial images and computational processing is emerging as one of the solutions used in precision agriculture to observe the nutritional status of plants. The objective of this study is therefore to associate the nitrogen content and dry weight of the aerial part of maize plants (DW) with the vegetation indices obtained by multispectral aerial images (NDVIA and NDREA), and with the SPAD index and the Greenseeker NDVI, in the vegetative stage V6. To this end, ran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
3
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 18 publications
0
3
0
1
Order By: Relevance
“…As highlighted in Table 2, most of the studies related to the use of VIs in maize research focused on NDVI index alone or in combination with other VIs. Generally, researchers used NDVI to discriminate maize crops [45][46][47], to predict yields [6,[48][49][50][51][52], to detect stress [53], and to make decisions related to fertilization [49]. While NDVI is a prominent choice, other VIs such as EVI and GNDVI were also employed in maize research, depending on the specific objectives and data available.…”
Section: Maize Cropmentioning
confidence: 99%
See 1 more Smart Citation
“…As highlighted in Table 2, most of the studies related to the use of VIs in maize research focused on NDVI index alone or in combination with other VIs. Generally, researchers used NDVI to discriminate maize crops [45][46][47], to predict yields [6,[48][49][50][51][52], to detect stress [53], and to make decisions related to fertilization [49]. While NDVI is a prominent choice, other VIs such as EVI and GNDVI were also employed in maize research, depending on the specific objectives and data available.…”
Section: Maize Cropmentioning
confidence: 99%
“…Promising results could be achieved also by using UAV data, as long as the operator of the equipment is highly trained and performs the requested adjustments according to each crop specificity. Hoss et al [48] assessed the NDVI of a maize crop by employing a DJI Matrice 200 RPA drone fitted with a multispectral camera. Their findings revealed that flying at higher altitudes during data collection (90 m and 120 m) yielded more accurate results compared to low altitudes (30 m and 60 m).…”
Section: Maize Cropmentioning
confidence: 99%
“…Therefore, above-ground forage mass parameters are often used as indicators of available forage quality and quantity for the animal unit, providing information for farm management [ 17 ]. Traditional forage mass analysis entails laborious and destructive actions [ 18 , 19 ]. These methods have low sampling precision, as they are based on random sample means without considering the spatial variation of biomass [ 20 , 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…Destaca-se a utilização do medidor SPAD (Soil Plant Analysis Development) (modelo SPAD-502), ferramenta que mede o índice SPAD (Soil Plant Analysis Development) para avaliar de forma simples, rápida, e não destrutiva, o verde ou conteúdo relativo de clorofila das folhas (FELSEMBURGH e TRIBUZY, 2012). O clorofilômetro SPAD apresenta resultados promissores na estimativa do teor de nitrogênio na cultura do milho (HOSS et al, 2020;RHEZALI, A., & AISSAOUI, 2021) podendo ser ferramenta bastante eficaz na quantidade recomendada de N sem afetar a produtividade do milho (ISLA et al, 2020).…”
Section: Introductionunclassified